Relationship between Religious Orientation, Emotional Maturity and Identity Styles with Marital Infidelity - Samaneh Ebrahimi Khasmakhi; Afshin Salahin (European Scientific Journal, ESJ, 2018)
Marital infidelity is a multi-faceted problem that has the tendency of an interpersonal and environmental dimension. This paper focuses on investigating the relationship between religious orientation, emotional maturity, and identity styles with talent of marital infidelity in married women and men in Tehran, Iran. The research method was by correlation and the study sample consists of 121 subjects (62 women and 59 men) who were selected by available sampling method. Marital infidelity, religious orientation, emotional maturity, and identity styles questionnaires were used to collect data. Correlation method and regression analysis was used to determine the predictive factors. The results indicated that there was no significant relationship between religious orientation and marital infidelity. On the other hand, there was a positive and significant relationship between emotional maturity and marital infidelity. The results also showed that from the four identity styles, only confused and committed identity styles are related to marital infidelity. Regression results also showed that commitment and emotional maturity in two steps significantly predicted 22% variance of marital infidelity.